Generalized Combination-combination Synchronization of Chaos in Identical Orders Chaotic Systems - Ojo, K.S.; Njah, A.N.; Olusola, O.I. (Journal of Applied Nonlinear Dynamics, 2026)
This paper proposes a generalized combination-combination synchronization scheme (GCCS) for identical order chaotic systems. Using the active backstepping technique. Based on active backstepping technique, suitable controllers are designed to achieve GCCS for any desired scaling factor among four chaotic Josephson junctions (JJs) evolving from different initial conditions. Numerical simulations are carried out to verify the feasibility and effectiveness of the proposed GCCS via active backstepping technique. The result shows that the proposed GCCS could be used to vary the JJ signal to any desired level and provide higher security in information transmission due its complex dynamical formulation.